Analytical Methods for Os Isotope Ratios and Re-PGE Mass Fractions in Geological Samples - Chu, Zhuyin (Frontiers in Chemistry, 2021)
The recent advances for analytical methods of Re-Os and PGE in geological materials including sample dissolution, chemical separation, mass spectrometric determinations, as well as the developments of matrix-matched reference materials for data quality control are thoroughly reviewed. Further, the in-situ measurement methods for Re-PGE mass fractions and 187Os/188Os ratios, as well as the measurement methods for stable isotope ratios of Re and PGE are also briefly reviewed. This review stands as a comprehensive reference for researchers to consider for the development of measurement methods for Re-PGE mass fractions and 187Os/188Os ratios in geological materials.